Antibodies Against Phosphorylcholine Among 60-Year-Olds: Clinical Role and Simulated Interactions - Samal, Shailesh Kumar; Panda, Pritam Kumar; Vikström, Max; Leander, Karin; de Faire, Ulf; Ahuja, Rajeev; Frostegård, Johan (Frontiers in Cardiovascular Medicine, 2022)
Aims Antibodies against phosphorylcholine (anti-PC) are implicated as protection markers in atherosclerosis, cardiovascular disease (CVD), and other chronic inflammatory conditions. Mostly, these studies have been focused on IgM. In this study, we determined IgG, IgG1, and IgG2 anti-PC among 60-year-olds. Methods Based on a 7-year follow-up of 60-year-olds (2,039 men and 2,193 women) from Stockholm County, we performed a nested case-control study of 209 incident CVD cases with 620 age- and sex-matched controls. Anti-PC was determined using ELISA. We predicted the binding affinity of PC with our fully human, in-house-produced IgG1 anti-PC clones (i.e., A01, D05, and E01) using the molecular docking and molecular dynamics simulation approach, to retrieve information regarding binding properties to PC. Results After adjustment for confounders, IgG and IgG2 anti-PC showed some significant associations, but IgG1 anti-PC was much stronger as a protection marker. IgG1 anti-PC was associated with an increased risk of CVD below 33rd, 25th, and 10th percentile and of stroke below 33rd and 25th, and of myocardial infarction (MI) below 10th percentile. Among men, a strong association with stroke was determined below the 33rd percentile [HR 9.20, CI (2.22–38.12); p = 0.0022]. D05 clone has higher binding affinity followed by E01 and A01 using molecular docking and further have been confirmed during the course of 100 ns simulation. The stability of the D05 clone with PC was substantially higher. Conclusion IgG1 anti-PC was a stronger protection marker than IgG anti-PC and IgG2 anti-PC and also separately for men. The molecular modeling approach helps in identifying the intrinsic properties of anti-PC clones and atomistic interactions with PC.